Structure of CrmE, a virus-encoded tumour necrosis factor receptor. - Graham, S; Bahar, M; Abrescia, N; Smith, G; Stuart, D; Grimes, J (2007)
Vaccinia virus (VACV), the smallpox vaccine, encodes many proteins that subvert the host immune response. One of these, cytokine response modifier E (CrmE), is secreted by infected cells and protects these cells from apoptotic challenge by tumour necrosis factor alpha (TNFalpha). We have expressed recombinant CrmE from VACV strain Lister in Escherichia coli, shown that the purified protein is monomeric in solution and competent to bind TNFalpha, and solved the structure to 2.0 A resolution. This is the first structure of a virus-encoded tumour necrosis factor receptor (TNFR). CrmE shares significant sequence similarity with mammalian type 2 TNF receptors (TNFSFR1B, p75; TNFR type 2). The structure confirms that CrmE adopts the canonical TNFR fold but only one of the two "ligand-binding" loops of TNFRSF1A is conserved in CrmE, suggesting a mechanism for the higher affinity of poxvirus TNFRs for TNFalpha over lymphotoxin-alpha. The roles of dimerisation and pre-ligand-assembly domains (PLADs) in poxvirus and mammalian TNFR activity are discussed.